Legal Settlement Of Breach Of Bank Loan Agreement With Fair Guarantees - Vic S, Binsar Jon; Iryani, Dewi (Ilmu Hukum Prima (IHP), 2025)
Debt is an integral part of the business world, particularly as a solution for entrepreneurs experiencing capital shortages. Financial institutions, particularly banks, act as facilitators providing credit with or without collateral. A crucial aspect of credit provision is the existence of collateral to protect the bank, as the creditor, from the risk of default by the debtor. This study aims to analyze the legal resolution of default in bank loan agreements secured by certificates in a fair manner, using the case study of Decision Number 141/Pdt.GS/2021/PN Byw. This study uses a normative juridical method with a descriptive-analytical approach, based on primary, secondary, and tertiary legal materials. The results of the study indicate that legally, banks have the right to execute collateral if the debtor is in default, according to Article 6 and Article 20 of the Mortgage Law. However, in practice, the execution process is often faced with resistance from debtors who lack good faith, including the filing of new lawsuits to hinder the execution. In the context of justice, the judge in the decision of the case did not immediately grant all of the bank's demands, but instead considered the principle of substantive justice by rejecting some of the fine demands that were deemed disproportionate. This approach aligns with the views of legal philosophers such as Aristotle, John Rawls, and the progressive legal thought of Satjipto Rahardjo, who emphasized that justice is not merely formal equality but also treatment appropriate to the social and moral context. Therefore, the court's decision in this case demonstrates the implementation of guarantee law in accordance with statutory regulations and reflects the value of justice in resolving banking disputes.